Art, anthropology, and contested heritage : ethnographies of TRACES - Schneider, Arnd, 1960- (Bloomsbury Academic, 2020)
"This book presents innovative and creative ethnographic perspectives on the intersection between art, anthropology, and contested cultural heritage resulting from ethnographic and artistic research by the TRACES project (an interdisciplinary research project funded by the EU's Horizon 2020 programme involving a collaboration between institutional partners in 11 European countries). The case studies in this volume critically assess and evaluate how and in which arrangements artistic/aesthetic methods and creative everyday practices contribute to strengthening communities both culturally and economically. They also explore the extent to which these methods emphasize minority voices and ultimately set in motion a process of reflexive Europeanisation from below which unfolds within Europe and beyond its borders. At the heart of these ethnographic case studies is the development of a new way of transmitting contentious cultural heritage, which responds to the present situation in Europe of unstable political conditions and a sense of Europe in crisis. With chapters looking at difficult art exhibitions on colonialism, death masks, Holocaust memorials and skull collections, the contributors articulate a response to the crisis in current economic-political conditions in Europe and advances brand new theoretical groundwork on the configuration of a renewed European identity. Through combining studies of heritage within museums, this volume will appeal to students and scholars of anthropology, heritage and museum studies, and visual culture"--